KINESIKA DALAM TARIAN MODERN BREAKDANCE (FINAL INTERNATIONAL BATTLE OF THE YEAR 2015): SEBUAH ANALISIS SEMIOTIK - KOYONGKAM, YASINTA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This study entitles â€œKinesika Dalam Tarian Modern Breakdance (Final International Battle of The Year 2015): Sebuah Analisis Semiotikâ€. Kinesics is a sign that is produced by humanâ€™s body movements. Every sign of body movements produced by human has meaning and itâ€™s used for nonverbal communication. This study is an attempt to identify, classify, and analyze the body movements or kinesics produced by b-boys in the video documentation of International Battle of The Year 2015 Final. The data are collected through the authorâ€™s explanation about the category of kinesics as a sign to communicate nonverbally. The writer uses the theory of Ray L. Birdwhistell to identify and classify the data. The writer uses the theory of Roland Barthes which states that connotation is a new meaning that gives user the sign in accordance with wishes, background of knowledge, or a new convention that exists in a society. The results of this research show that based on the theory of Birdwishell, there are three kind of kinesics on b-boys that appears during breakdance. Those are kinesics as facial expression, kinesics as gestures, and kinesics as postures. The meanings of kinesics that appears are the sign of orders, notices, asking, confidence, support, enthusiasm, waiting, calling, stops, compliment, preparation, self greatness, blow up, instructions, information, and breakdance is over. The writer hopes that this study will help the reader to understand about semiotics especially on kinesics as one of nonverbal signs and how it works in communication. Â Keywords: Body movements, Kinesics, Semiotic Analysis, Breakdance, Final International Battle of The Year 2015